Management of functional dyspepsia: a clinical practice review - Naliuka, Hanna; Byjoś, Ewa; Milewska , Kamila; Bury, Karolina; Fabiś , Katarzyna; Młynarczyk, Katarzyna; Zbylut, Mateusz; Mateja, Patrycja; Buczek, Sylwia; Mstowska, Weronika (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Functional dyspepsia (FD) is a common disorder of gut–brain interaction characterized by chronic upper gastrointestinal symptoms without structural disease. Its heterogeneous mechanisms and limited treatment efficacy remain major clinical challenges. This review summarizes evidence published between 2020 and 2025 on adult FD management and proposes a practical, phenotype-guided therapeutic approach for everyday clinical practice. State of knowledge: All patients with dyspeptic symptoms should undergo testing for Helicobacter pylori, with eradication therapy recommended for all infected individuals to identify H. pylori–associated dyspepsia and prevent misclassification as FD. In confirmed FD, proton pump inhibitors represent first-line pharmacotherapy, providing modest but clinically relevant symptom improvement. H₂-receptor antagonists may be used as second-line or on-demand therapy. In patients with postprandial distress syndrome, prokinetic agents are preferred. However, safety concerns limit long-term use of metoclopramide and domperidone, whereas itopride and cinitapride offer more favourable efficacy–tolerability profiles. For epigastric pain–predominant FD or treatment-refractory disease, low-dose tricyclic antidepressants show the strongest evidence among neuromodulators, while SSRIs and SNRIs are not recommended. Selected adjunctive therapies offer additional benefit with good short-term safety. Summary: Management of FD should be systematic, stepwise and phenotype-driven, combining pharmacological therapy and evidence-based adjunctive interventions. Although treatment effects are modest, individualized combination strategies can achieve meaningful and sustained symptom improvement in many patients.